Namibia's red line : the history of a veterinary and settlement border - Miescher, Giorgio (Palgrave series in African borderlands studies., 2012)
Based on archival sources and oral history, this book reconstructs a border-building process in Namibia that spanned more than sixty years. The process commenced with the establishment of a temporary veterinary defence line against rinderpest by the German colonial authorities in the late nineteenth century and ended with the construction of a continuous two-metre-high fence by the South African colonial government sixty years later. This 1250-kilometre fence divides northern from central Namibia even today. The book combines a macro and a micro-perspective and differentiates between cartogr.